Deadly syringes: type VI secretion system activities in pathogenicity and interbacterial competition - Kapitein, Nicole; Mogk, Axel (Current opinion in microbiology, 2013)
Among specialized bacterial secretion systems, the most widespread is the type VI secretion system (T6SS). This transports effector molecules into target cells in a single, cell-contact dependent step. T6SSs are structurally related to the cell-puncturing device of tailed bacteriophages and predicted to function as contractile injection machineries that perforate eukaryotic and prokaryotic target membranes for effector delivery. Activities of T6SSs can play important roles in virulence by modifying the eukaryotic host cytoskeleton through actin crosslinking. They are also efficient weaponry in interbacterial warfare and provide a fitness advantage by hydrolyzing cell walls of opponent bacteria. The role of T6SSs in interbacterial competition might enable pathogens to outcompete commensal bacteria and facilitate host colonization.
Gesehen am 15.04.2021